2015
DOI: 10.1097/sap.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Role of Intraoperative Core Temperature in Free Tissue Transfer

Abstract: Intraoperative hypothermia posed significant risk of flap infection with no benefit to anastomotic patency in free tissue transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…46 However, hypothermia has been associated with perioperative complications in the majority of studies. 11,12,47 In an animal study, intraoperative hypothermia reduced flap flow and postocclusive hyperemia. 47 Intraoperative hypothermia (minimum core temperature, <35°C) has also been correlated with perioperative complications in patients.…”
Section: Patient Temperaturementioning
confidence: 98%
“…46 However, hypothermia has been associated with perioperative complications in the majority of studies. 11,12,47 In an animal study, intraoperative hypothermia reduced flap flow and postocclusive hyperemia. 47 Intraoperative hypothermia (minimum core temperature, <35°C) has also been correlated with perioperative complications in patients.…”
Section: Patient Temperaturementioning
confidence: 98%
“…Recently, the role of intraoperative hypothermia has gained attention. [13][14][15][16] Free-flap reconstructions are regularly performed in two operating teams. 17 This exposes large skin surface areas, which increases patients' susceptibility to hypothermia.…”
mentioning
confidence: 99%
“…17 This exposes large skin surface areas, which increases patients' susceptibility to hypothermia. 15,18 In general, hypothermia causes peripheral vasoconstriction, an increase in blood viscosity and a reduced blood flow, which can ultimately lead to increased thrombogenic potential. 14,[19][20][21] Conversely, therapeutic hypothermia has been shown to reduce hypoxemia and ischemia in a wide range of different settings, such as acute myocardial infarction 22,23 or organ preservation, prior to transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 In addition, normothermia has been shown to reduce surgical-site infection. 10,11 Hypothermia causes impaired platelet function, increased blood loss and transfusion requirements, prolonged hospitalization, 12 and increased cardiac events in patients with coronary artery disease. 13 A Cochrane review of 24 studies found that using warm intravenous fluids helped prevent hypothermia better than room-temperature fluids.…”
Section: Anesthesia Considerationsmentioning
confidence: 99%